INFLUENCE OF ANEMIA ON THE COURSE OF PREGNANCY AND THE BODY OF NEWBORN CHILDREN - Djurabaev, A.A. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2025)
Anemia, as a clinical syndrome, is characterized by a decrease in the level of hemoglobin in the blood, which leads to a decrease in the transport capacity of the blood to transfer oxygen to tissues. During pregnancy, anemia can have a negative impact on the health of the mother and fetus, changing the course of pregnancy and increasing the risk of developing various pathological conditions. At the same time, anemia can affect the health of newborns, increasing the possibility of developing hypoxia, growth retardation and other pathologies.